Perception of Patient Safety Incident Reporting System among Healthcare Workers in Hospital - Dr.Saad owdah alsohail, ‏Hisah saeid nwar AlJaeeid, ‏FATEN SAEED ALI ALHRTHI, Ali lbarhim ali Al Tarahi, ABDULRHMAN SAAD ALKAREMI; Khalid Awad Zoogm Alwadee, SAUD KHALLUFAH ALAHMARI, sami hadi saleh alsawidan, ‏Abdulaziz Mohammed moied Albarqi (Journal of International Crisis and Risk Communication Research, 2024)
1. Introduction to Patient Safety Incident Reporting Ensuring patient safety, which means the reduction in the risk of unnecessary harm associated with health care to an acceptable minimum, should be the primary concern of healthcare. Patient safety is defined as the absence of preventable harm to a patient during the process of healthcare and reducing the gap between the care the patient receives and the care that the patient should receive. Poor communication and lack of teamwork, fatigue, inadequate equipment, medication errors, and poor environment are some of the causes that lead to patient safety incidents. Patient safety should be a top priority in healthcare institutions. It is a fundamental right of any patient to receive safe care. Methods This study was conducted in a university hospital using a multi-method design to explore the perception of healthcare workers regarding a patient safety incident reporting system. A survey questionnaire was initially used to collect views from a large number of healthcare workers. A series of key focus group interviews were also scheduled to collect in-depth perceptions from a subgroup of these healthcare workers, which served to complement the initially quantitative research findings. Based on the perceptions surveyed and discussed in the semi-structured focus group interviews, significant aspects of a patient safety incident reporting system in the hospital, such as barriers and facilitators to its utilization, were identified. The mutual pattern of a validity assessment confirmed that the perceived factors enabling healthcare workers to make full use of the patient safety reporting system in the hospital. Conclusion The findings showed that there were a small number of patient safety incident reports by healthcare workers. The healthcare workers generally perceive the current reporting system as time-consuming and having the potential to become a channel for unfair judgment. They were inclined to provide reports only if they were asked specifically to do so. However, the majority were willing to provide feedback for recommended patient safety improvements. There are also no large differences in perception of the reporting system between public and private hospital staff. Hence, for the Malaysian healthcare regulatory body, the results of this study are important knowledge provided by the healthcare workers themselves on the actual situation of the patient safety incident reporting system in its current form. This in-depth insight can be used to develop recommendations that lead to a more realistic and effective information system. While regulatory bodies must address the problems faced on the frontline, the detailed results of a focus group discussion can be used internally by the hospitals. The focus group discussion can be the starting point of an overall patient safety initiative. It can be used to assess how such a step can be performed, and what needs to be done to improve the current situation. The regular solicitation of feedback from the healthcare workers working on the frontline can improve the quality and usefulness of patient safety incident reports. This would help the regulatory bodies to monitor and improve the quality of patient safety in a more active and refined manner. The need for regulatory bodies to play their role accurately and constantly in adverse incident reporting, feedback, and communication is critical indeed.